1993
DOI: 10.1029/92ja02019
|View full text |Cite
|
Sign up to set email alerts
|

EXOS D (Akebono) observations of molecular NO+ and N2+ upflowing ions in the high‐altitude auroral ionosphere

Abstract: We report observations of molecular upflowing ions in the high-altitude auroral ionosphere by the EXOS D (Akebono) suprathermal mass spectrometer (SMS). At Akebono altitude, the occurrence of molecular upflowing ions was rare and was often confined in latitudinal extent, in both the dayside and the nightside. In the dayside, molecular upflowing ions were observed up to about 85' A, inside and up to -10 ø poleward of the cleft. In the nightside, they were generally located at lower invariant latitudes (-60ø-75ø… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
85
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(93 citation statements)
references
References 37 publications
8
85
0
Order By: Relevance
“…Recent observations with satellites such as Akebono (EXOS-D) and GEOTAIL have shown that thermal ions, including not only light ions H + and He + but also heavy ions O + and NO +¯o w out of the polar ionosphere and they are found in the lower magnetosphere (Watanabe et al, 1992;Abe et al, 1993a, b;Yau et al, 1991Yau et al, , 1993Yau et al, , 1995 and in the lobe magnetosphere (Mukai et al, 1994;Hirahara et al, 1996;Seki et al, 1996Seki et al, , 1998. A very comprehensive review of the terrestrial plasma source obtained from the DE mission was given by Chappell (1988).…”
Section: Introductionmentioning
confidence: 99%
“…Recent observations with satellites such as Akebono (EXOS-D) and GEOTAIL have shown that thermal ions, including not only light ions H + and He + but also heavy ions O + and NO +¯o w out of the polar ionosphere and they are found in the lower magnetosphere (Watanabe et al, 1992;Abe et al, 1993a, b;Yau et al, 1991Yau et al, , 1993Yau et al, , 1995 and in the lobe magnetosphere (Mukai et al, 1994;Hirahara et al, 1996;Seki et al, 1996Seki et al, , 1998. A very comprehensive review of the terrestrial plasma source obtained from the DE mission was given by Chappell (1988).…”
Section: Introductionmentioning
confidence: 99%
“…The mode used in the Akebono study measured at a maximum energy of 70 eV. Yau et al (1993) reported that typical dayside energies were 5±20 eV and that typical nightside energies were larger but no energy range was speci®ed. It is however, quite clear that very e cient energisation of the molecular ions must take place.…”
Section: First Resultsmentioning
confidence: 99%
“…Since the simultaneous appearance suggests that they have the same velocity at each moment, the heavy ion is most likely O+ (mass ratio 16) rather than N+ (mass ratio 14) or C+ (mass ratio 12), if the heavy ions and H+ originate from the same region. This event took place during the storm time when N+ was expected to be nearly as rich as O+ in the magnetosphere (Yau et al, 1993); yet the energy band (width in %) of injecting ions is about the same for proton and heavy ions, indicating that one species (O+) dominated among C+, N+ and O+.…”
Section: Midday Heavy Ion Injection Eventmentioning
confidence: 99%
“…Yet, some of the plasma injections into the ionosphere reported in the past (without mass spectrometers) are considered to contain substantial heavy ions. We pedagogically call them O+ but they could also contain N+, C+ or Na+ (Chappell et al, 1982;Yau et al, 1993) …”
Section: Introductionmentioning
confidence: 99%